Skizofrenia Paranoid - Salsabila Salsabila; Mila Astari Harahap (Lembaga Pengembangan Kinerja Dosen, 2025)
Paranoid schizophrenia is a condition of mental and behavioral disorders characterized by impaired thoughts, perceptions, feelings and consciousness of the patient is fully conscious and intellectually can still be maintained. According to WHO, the prevalence of schizophrenia in 2021 reached 24 million people, and the prevalence of schizophrenia experiencing from 2019-2021 has increased by 54%. Patient Mr. Mr. Z said he was brought to Cut Meutia Hospital because he had a fight with his wife, and he had divorced his 3 wives. The patient said he did not want to eat because there was dirt in his food. The patient said that he heard whispering voices from his wife. The patient said he wanted to divorce his wife but she kept pursuing him. The patient said that he was beaten by his wife's brother. The patient said that he was taken for breaking the glass of a woman's house who insisted on having him. The patient said that he was a Messenger of Allah and he was upset because his power was taken away by a woman. The patient broke the glass because he was taking revenge on the woman who first broke the glass of his house and cellphone. The patient also said that he was given a lethal injection yesterday and his hand now hurts. Fluent speech, verbal and relevant contact, euthymic mood and dulled affect. The patient was given psychopharmacological therapy in the form of anti-psychotic drugs and the family was also given education about supportive therapy to the patient.